The effect of political connections on forward- looking information disclosure from the perspective of the stakeholder salience theory - Rusli, Mas Nordiana; Mohd Saleh, Norman; Hassan, Mohamat Sabri; Bagaan Abdullah, Mohd Hafizuddin Shah (Universiti Utara Malaysia, 2020)
This study examines the effect of political connections (PCONS) on firms’ disclosure of forward-looking information choices in the context of developing countries. Using multivariate regression of panel data comprising 360 firmyear observations of non-financial firms listed on Bursa Malaysia betweenyears 2014 and 2017, PCONS are found to be positively associated with disclosure of forward-looking information. However, such relationship only exists for non-financial forward-looking information. Using the stakeholder salience theory to further contribute to the body of knowledge, the strength of the connections suggests that a high composition of politically-connected directors on the board promotes greater information about the future in firms’ disclosure. The common connection through ownership of firms in emerging countries suggests the effective role of institutional shareholders in improving forecasting activities through high disclosure of forward-looking information. The study suggests a better appreciation of the hierarchical role of politically-connected directors on the board of types of forward-looking information presented to the stakeholders.